Suurten maito- ja viljatilojen suorituskyky ja sen kehittäminen - Sipiläinen, Timo (Helsingin yliopisto Taloustieteen laitos, 2003)
The objective of the study is to examine the economies of size on Finnish dairy and cereal farms. Economies of size are analysed using the concepts of productivity, efficiency and profitability. In productivity and efficiency analysis we apply data envelopment analysis on Finnish bookkeeping/FADN data. The study period covers 1989 - 2000. The effect of managerial ability on the realisation of size economies is also included as a part of the study. The study is completed by two case studies on managerial objectives and routines at the farm level. The results show a relatively high variation in the performance of farms. However, profitability and efficiency are relatively permanent properties since the rank correlation of them is statistically significant over the years. In general, productivity change is slow. Productivity change is based on technical change, which is often induced by farm growth. Profitability and efficiency are related to the size of farms but the changes in productivity and efficiency do not necessarily coincide with the growth of farms. Thus, making economies of size to realize through the growth of the farm is not straight forward. The case studies suggest that knowledge building is an essential part of successful management and growth. Even large Finnish farms are still relatively small. They are mainly operated by family labour, the manager being also responsible for a large part of production activities in practice. The threshold to hire permanent employees is high and finding seasonal competent workers is often difficult. Thus, the family labour supply is often a hard constraint for the farm growth in addition to the economic realities.
Keywords: Ma; tuottavuus; tehokkuus; kannattavuus; DEA; LP; maitotila; viljatila; productivity; efficiency; profitability; DEA; LP; dairy farm; cereal farm